KONSEP PEMERINTAHAN ISLAM IMAM KHOMEINI - Hartati Hartati (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2017)
Western democracy has ruined the eastern world, especially the Islamic world. For that Muslims should teach the Western people about the meaning of democracy. Khomeni is a the father of Iran's revolution of fundamentalism, it did not escape the thinking pattern influenced by mystics, philosophy and tasawuf based on the teachings of the Qur'an and Hadith. The concept of a Government that demanded the Muslims to plunge into the political scene to direct the life of the Islamic community in line with the laws of God, both in terms of relating to the Government and the community. Khomeini offered a new model of democracy which is based on the teachings of Islam with the mention